Vitrimer Chemistry Assisted Fabrication of Aligned, Healable, and Recyclable Graphene/Epoxy Composites - Chen, Jingjing; Huang, Hong; Fan, Jinchen; Wang, Yan; Yu, Junrong; Zhu, Jing; Hu, Zuming (Frontiers in Chemistry, 2019)
The alignment is a key factor to fully exploit the potential of graphene in reinforcement of polymer composites. However, it is still a challenge to orientate graphene in thermosets because of the insoluble and infusible features of the later. In this paper, we report a facile and scalable hot press method to fabricate aligned graphene nanoplate (GnP)/epoxy composites by utilizing the dynamic character of epoxy vitrimer. The bond exchange and topological rearrangement associated viscous flow of epoxy vitrimer during hot press allows the spontaneous orientation of GnP in matrix because the 2D structure and volume exclusion effect. SEM images demonstrate the orientation of GnP, while tensile test reveals the significantly increased reinforcement effect of GnP on matrix after hot press. Moreover, the dynamic reaction of epoxy vitrimer confers good healability and recyclability to the aligned composites as confirmed by the nearly fully recovered mechanical properties of the healed sample after cutting, and the recycled sample after grinding. This work is expected to provide new opportunity for fabrication of aligned thermosetting composites.